Super-enhancer DNA methylation in cancer: the mechanism of action and therapeutic directions - Bi, Yue; Zou, Kang; Wang, Ke (Frontiers in Oncology, 2025)
The interplay between DNA methylation and super-enhancer activity is emerging as a key focus in cancer research. Super-enhancers, a specialized class of enhancers, strongly activate transcription of their target genes due to their dense clustering with essential transcription factors (TFs) and cofactors. In cancer, especially, these super-enhancers control key oncogenic drivers and often display abnormal DNA methylation patterns that can repress or overexpress target genes in both solid and blood cancers. Furthermore, DNA methylation in the super-enhancer region has been found to influence their regulatory capacity. Although enhancers are typically characterized by low DNA methylation, dysregulated methylation at super-enhancers is seen in most malignancies, affecting TF and chromatin regulator recruitment. Hypomethylation at these sites often accompanies oncogene hyperactivation, while hypermethylation can repress tumor suppressor mechanisms. Recent research highlights DNA methylation as a promising source of cancer biomarkers. This review examines the intricate relationship between DNA methylation and super-enhancer activity in cancer, concentrating on how methylation regulates super-enhancers, modulates oncogene expression, promotes oncogenesis, and serves as a target for novel oncology therapies.